1972
DOI: 10.1152/ajplegacy.1972.223.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal deficiencies and the metabolic adaptations of rats to training

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 0 publications
3
8
0
2
Order By: Relevance
“…3) demonstrate the effectiveness of the anti-GHRH antisera. Our results are consistent with the studies of Goldberg (19) and Gollnick and lanuzzo (20) who showed that muscle hypertrophy and increases in muscle SDH can occur either as a compensatory mechanism or in response to exercise in mature. hypophysectomized rats.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…3) demonstrate the effectiveness of the anti-GHRH antisera. Our results are consistent with the studies of Goldberg (19) and Gollnick and lanuzzo (20) who showed that muscle hypertrophy and increases in muscle SDH can occur either as a compensatory mechanism or in response to exercise in mature. hypophysectomized rats.…”
supporting
confidence: 93%
“…Hypophysectomy has been used previously in the mature rat to obliterate any possible effect of exercise on GH secretion (19,20), but this invasive surgical technique is technically more difficult in younger rats, results in reduced spontaneous physical activity, and requires the administration of other pituitary hormones to maintain health. As an alternative approach to attenuate GH secretion, we administered anti-GHRH antiserum.…”
mentioning
confidence: 99%
“…Associated with these changes, the authors also observed a significant improvement in running time to exhaustion when compared with an untrained control group (186±18 min vs. 29±3 min). Similar findings have subsequently been observed by other groups using guinea pigs (Barnard et al, 1970), rats (Gollnick & Ianuzzo, 1972) and later humans (Morgan et al, 1971). Using a single-leg cycling design, Morgan et al (1971) observed that an increase in mitochondrial protein content was largely due to increases in mitochondrial size (i.e.…”
Section: Exercise-induced Mitochondrial Biogenesissupporting
confidence: 81%
“…Electronmicroscopy of hypothyroid muscle suggests an increase in the number of mitochondria (41), while the yield ofmitochondrial protein has been reported to be both normal (4) or decreased (6,8). Most authors, however, agree that the activities of those muscle enzymes that serve as markers of mitochondria are reduced in hypothyroidism (4)(5)(6)(7)(8)(9). This reduction seems more pronounced in red muscle (7)(8)(9) and its net effect on mixed muscles is not clear.…”
Section: P Nmrmentioning
confidence: 99%
“…Furthermore, the activities of several key mitochondrial enzymes are reduced (4)(5)(6)(7)(8)(9). The latter is more pronounced in slow twitch, red muscles compared with fast, white muscles (7,8).…”
Section: Introductionmentioning
confidence: 99%